Patient autonomy - lbugami, Muneerah; El Alem, Usamah (International Journal of Medicine, 2021)
Patient autonomy is one of the most important ethical values in the health care practice. Patients’ autonomy means the right of patients to make decisions about their medical care without their health care provider trying to influence the decision. Patients’ autonomy allows health care providers to educate the patients but do not allow them to make the decision for the patients.